Application of the SARIMA-LSTM model to evaluate the effectiveness of interventions for Visceral Leishmaniasis - Mengchen Han; Chongqi Hao; Zhiyang Zhao; Peijun Zhang; Bin Wu; Lixia Qiu (Journal of Infection in Developing Countries)
Introduction: This study proposes a combined Seasonal Autoregressive Integrated Moving Average and Long Short-Term Memory (SARIMA-LSTM) model to enhance the accuracy of evaluating the effectiveness of visceral leishmaniasis prevention and control efforts in Yangquan, China.